Waldenström Macroglobulinemia of the orbit: A diagnostic challenge. Issue 1 (January 2022) - Adiga, Sushant; Mehta, Aditi; Singh, Usha; Singh, Charanpreet; Sharma, Rintu; Banerjee, Nirmalya; Lad, Deepesh; Rastogi, Pulkit
Purpose: Ocular adnexal lymphomas (OAL) constitute 55% of all orbital tumors. Waldenström Macroglobulinemia (WM) presenting as an orbital mass with diffuse extraocular muscle (EOM) involvement is rare. We report an elderly patient who presented to the ophthalmologist for an orbital mass which on evaluation, turned out to an ocular adnexal WM. Observations: A 75 years old man presented with a palpable mass in the left anterior superior orbit and bilateral restricted ocular motility in all gazes. Computed tomography scan revealed a hyperdense mass with diffuse thickening of extraocular muscles and enlarged lacrimal gland on the left side. Incisional biopsy of the mass revealed a lymphoproliferative neoplasm with plasmacytic morphology. Immunohistochemistry (IHC) of the orbital mass as well as the bone marrow was sought, lymphoplasmacytic lymphoma (CD20+, CD38+, MUM1+, BCL 2+, CD3−, CD5−, CD10−, CD23−, cyclin D1). Bone marrow flow cytometry showed CD5−, CD10− kappa restricted B cell neoplasm. Serum analysis significantly elevated IgM levels. This indicated a diagnosis of ocular adnexal Waldenström Macroglobulinemia. Conclusion and importance: This case highlights the importance of clinical evaluation, histopathology, and immunohistochemistry for phenotyping of ocular adnexal lymphomas.